Comparative study for connecting new flare capacity to existing flare Systems - Fouad, Mohamed Shamandy; Shehata, Walaa Mahmoud; Shehata, Walaa Mahmoud; Gad, Fatma Khalifa; Abdelaleem, Nabil Abdelsadek (International Journal of Psychosocial Rehabilitation, 2020)
Process facility operations are equipped with flare system to dispose flammable, toxic, or corrosive vapors to an environmentally acceptable gas for release to the atmosphere from both normal operational venting and relief during abnormal conditions. For safe incineration and radiation considerations flares are located at a remote point from the plant.Flare system when designed is to be limited for a certain capacity for a relieved gas; in addition, it may be designed in excess for future process facilities which may be further added to an existing one. KHALDA Petroleum Company is an owner company of oil and gas plants in Egypt. The company started a remote facility in 2005 named as "QASR start of line" which equipped with a limited flaring system capacity of 416,800 kg/hr for each flare related to phases PH-1 and PH-2. After 10 years of operation the wells depletion occurred which affected the production capacity and hence the company decided to maintain the productivity. A new compression project is designed to improve recovery as the reservoir production rate and pressure decline. The new compression projectfacilities vent and disposal need a flare systemin case of the emergency. This paper discusses two different scenarios available for connecting the new compression project facilities vent and disposal system either to the existing flare systems or to another destination, which better, safer and more economic.